2004
DOI: 10.1086/426025
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Surveillance in the United States of Macrolide-Resistant Pediatric Pharyngeal Group A Streptococci during 3 Respiratory Disease Seasons

Abstract: The macrolide resistance rate among pharyngeal GAS was <5% and was stable over the 3 seasons. However, rates varied among sites each year. There was no evidence of spread of a specific resistant clone, increasing clindamycin resistance, or escalation in median erythromycin MICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 43 publications
3
46
2
4
Order By: Relevance
“…However, we did not detect any significant distribution in macrolide or tetracycline-resistant isolates. The heterogeneity of emm types among macrolide-resistant and tetracycline-resistant isolates in the present study is compatible with some reports 37 and contrasts with the others 14,19,26,27,30,39 . Montes et al reported an association between emm77 and tet(M).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, we did not detect any significant distribution in macrolide or tetracycline-resistant isolates. The heterogeneity of emm types among macrolide-resistant and tetracycline-resistant isolates in the present study is compatible with some reports 37 and contrasts with the others 14,19,26,27,30,39 . Montes et al reported an association between emm77 and tet(M).…”
Section: Discussionsupporting
confidence: 91%
“…8,29,33,39 Low erythromycin resistance rates (0.6%-6.8%) were reported in some countries. 14,15,21,23,25,28,30,37 Our erythromycin resistance rate was similar to rates in the United States (9.6%), 19 Germany (12.7%), 4 and Greece 280 DUNDAR ET AL.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The strains with emm28 showed a high ERY resistance rate (58.3%), suggesting that strains with this emm genotype are highly resistant. All erm(B)-positive ERY-resistant GAS isolates had an emm28 genotype, which accounts for 50% and 70% of erm(B)-positive ERY-resistant GAS isolates in North America [21] and France [6], respectively. In our previous study (2002), the ERY resistance rate of emm12 strains was 63%, and most of them had the cMLSB phenotype, whereas emm18 and emm75 strains had the M phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is the only drug that is given in a 5-day course as opposed to a 10-day course for all the other antibiotics. Although there are no strains of GAS resistant to penicillin, amoxicillin and cephalosporins, GAS susceptibility to macrolides varies depending on the region and the level of consumption, with the percentage of resistant strains reaching over 25% in some countries [59,60]. Since the susceptibility of the given GAS strain to macrolides is unpredictable, treatment with these drugs must be always preceded by performing antibiotic susceptibility test [7,28].…”
Section: Treatment Optionsmentioning
confidence: 99%